Consequences of Interstitial Cystitis/Bladder Pain Symptoms on Women’s Work Participation and Income: Results from a National Household Sample - Beckett, Megan K. (2013)
PURPOSE: To describe differences in work participation and income by bladder symptom impact and comorbidities among women with interstitial cystitis/bladder pain syndrome (IC/BPS). MATERIALS AND METHODS: Cross-sectional data from2767 respondents under age 65 identified with IC/BPS symptoms analyzed. The data are from the RAND Interstitial Cystitis Epidemiology (RICE) survey and include retrospective self-reports of IC/BPS impact, severity, years since onset, and related comorbidities (depressive symptomology, number of conditions), work participation and income, and personal characteristics. Multiple regressions predicted five current work outcomes: works now, kept from working by pain, missed work days, days worked when bothered by symptoms, and real income change since symptom onset. RESULTS: Controlling for work status at symptom onset and personal characteristics, greater bladder symptom impact predicted greater likelihood of not now working, kept more days from working by pain, missed more work days, and working more days with symptoms. More depressive symptomology and greater number of co-morbidities predicted reduced work participation. Women experienced no growth in real income since symptom onset. Measures of symptom severity were not associated with any of the economic outcomes. CONCLUSIONS: Greater IC/BPS symptom impact, depressive symptomology, and count of comorbidities (but not symptom severity) were each associated with less work participation and leveling of women’s long-term earnings. Management of bladder symptom impact on non-work-related activities and depressive symptomology may improve women’s work outcomes.